Causes and effects of wine tourism development in organizational context: The case of Alentejo, Portugal. (January 2018) - Lavandoski, Joice; Vargas-Sánchez, Alfonso; Pinto, Patrícia; Silva, João Albino
Companies with innovative behavior seek differentiation and are constantly reconciling needs and internal objectives with new market opportunities and restrictions imposed by the institutional framework. The involvement of the wineries with the service sector, by adapting to wine tourism, raises an innovative process which requires some organizational change. This study deals with this issue, arguing that the wineries' change process toward wine tourism development may occur as a result of internal drivers and external pressures. In this sense, the wineries are analyzed through two different points of view: an intraorganizational perspective with the dynamic capability approach, and an interorganizational perspective with the institutional theory. Structural equation modeling methodology is used to estimate and validate the model, which aims to explain the causes and effects of wine tourism development. Results support the propositions that through wine tourism development, the wineries create, extend, and modify their processes, building and using dynamic capabilities, whereas institutional factors shape firms' behavior and ensure social legitimacy, besides improving their organizational performance.